2013
DOI: 10.1152/ajpregu.00406.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term dietary nitrate supplementation on blood pressure, O2uptake kinetics, and muscle and cognitive function in older adults

Abstract: AM. Effects of shortterm dietary nitrate supplementation on blood pressure, O 2 uptake kinetics, and muscle and cognitive function in older adults. Am J Physiol Regul Integr Comp Physiol 304: R73-R83, 2013. First published November 21, 2012 doi:10.1152/ajpregu.00406.2012 Ϫ ) supplementation has been shown to reduce resting blood pressure and alter the physiological response to exercise in young adults. We investigated whether these effects might also be evident in older adults. In a double-blind, randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
213
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 206 publications
(254 citation statements)
references
References 84 publications
31
213
9
1
Order By: Relevance
“…Again this used a higher daily dose of 9.6 mmoles of nitrate, with the last supplementation episode 2.5 hours prior to BP measurement in laboratory conditions. 45 The unsupplemented plasma nitrite concentration in the diabetic cohort described in the present study -which had a median value and range of 232 nmol/L (200, 265) -was similar to that in the healthy subjects in Kelly et al's study (248 ± 182 nmol/l; mean ± SD). 45 The study by Sobko et al 46 examined the effect of a traditional Japanese diet.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Again this used a higher daily dose of 9.6 mmoles of nitrate, with the last supplementation episode 2.5 hours prior to BP measurement in laboratory conditions. 45 The unsupplemented plasma nitrite concentration in the diabetic cohort described in the present study -which had a median value and range of 232 nmol/L (200, 265) -was similar to that in the healthy subjects in Kelly et al's study (248 ± 182 nmol/l; mean ± SD). 45 The study by Sobko et al 46 examined the effect of a traditional Japanese diet.…”
Section: Discussionsupporting
confidence: 84%
“…45 The unsupplemented plasma nitrite concentration in the diabetic cohort described in the present study -which had a median value and range of 232 nmol/L (200, 265) -was similar to that in the healthy subjects in Kelly et al's study (248 ± 182 nmol/l; mean ± SD). 45 The study by Sobko et al 46 examined the effect of a traditional Japanese diet. The subjects had a mean age of 36 ± 10 years and again no difference was seen in systolic BP.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with a recent study in older individuals, where the V O 2 mean response time was speeded with BR supplementation (32). This may be related to the slower V O 2 kinetics that is typically found in older individuals and the potential to abate this through enhancing muscle O 2 delivery (57), via increasing NO bioavailability.…”
Section: Effects Of Br Supplementation On the Kinetic Profile Ofsupporting
confidence: 92%
“…Furthermore, the interindividual differences in the V O 2 response to exercise in normoxia evident in the current study, may have also contributed to the lack of statistically significant effects. It may be concluded that BR supplementation can (3,4,14,40,41,62), but does not always (present study, 5,8,32,66), alter the O 2 cost of exercise in normoxia.…”
Section: Effects Of Br Supplementation On the Kinetic Profile Ofmentioning
confidence: 52%
“…Increased dietary NO 3 -intake in the form of NO 3 --rich beetroot [11][12][13] or spinach [14,15] supplementation alone has also been shown to lower resting blood pressure. These findings are consistent with the emerging body of evidence to support improved vascular health following dietary NO 3 -supplementation (4-16 mmol·day -1 ) in younger [11][12][13] and older [16,17] normotensive adults, and in individuals with hypertension [18], peripheral artery disease [19] and heart failure [20]. Therefore, enriching the diet with NO 3 -, at a dose that can be readily achieved by a diet high in vegetables [4,7,9], might represent a practical and cost-effective intervention to lower cardiovascular disease morbidity and mortality.…”
Section: Introductionsupporting
confidence: 88%